Asthma exacerbations in the pediatric emergency area: Evaluation and prospects for improvement of pre-hospital care - Gonzalez-Uribe, Victor; Navarrete-Rodríguez, Elsy Maureen; Angeles-Tellez, Fernando Sebastián; Montiel-Gonzalez, Jose Angel; Colin-Rubio, Jorge; Gonzalez-Chavarria, Clara Fernanda; Mojica-Gonzalez, Zaira Selene (Allergologia et Immunopathologia, 2023)
Introduction: The frequency of visits to emergency department for asthma is a significant public health problem in pediatrics. This study aimed to identify the characteristics of children who visited the pediatric emergency department for asthma exacerbation and evaluated their therapeutic management prior to admission.Methods: A prospective study was conducted over a 6-month period in the pediatric emergency departments of five hospitals involving children aged 1–16 years admitted to the department with a clinical diagnosis of asthma exacerbation.Results: In all, 143 patients were enrolled in the study. Asthma episodes were moderate to severe in 69.2% of cases (n = 99). Initial treatment prior to admission to the emergency department was adequate in only 17.5% of cases (n = 25). Hospitalization for more than 24 h occurred in 18.2% (n = 26) patients. In children aged <3 years, viral infection was present in 91.4% cases (n = 64) and exacerbations were more severe in younger patients (P = 0.002) and children belonging to low-income stratum (P = 0.025). Only 17.4% (n = 25) were positive for SARS–CoV-2 (antigen test or polymerase chain reaction test), suggesting that the involvement of traditional respiratory viruses in asthma exacerbation continued even during pandemic. Regarding the pre-hospital care, 70.6% (n = 101) had received prior treatment, but this treatment was inadequate in 53.1% cases (n = 76).Conclusion: This study showed that asthmatic children and their families had little knowledge about the disease and that physicians must be sufficiently aware of current recommendations for managing asthmatic children. Admission to the emergency department for asthma could be avoided partially by better diagnosis and therapeutic education.